2014 International Conference on Advances in Electronics Computers and Communications 2014
DOI: 10.1109/icaecc.2014.7002429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of global feature in grid based framework for retrieving near duplicate images

Abstract: Major developments in image capture and image editing technologies have resulted in enormous increase of near duplicate data generation. This coupled with increased use of internet and availability of storage has led to large databases of such images being available. Hence, near-duplicate image detection and retrieval is an essential operation to refine image search results for effective user investigation. We have compared and analyzed global color features for near duplicate detection and retrieval using thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The study justified that the use of blurring as a preprocessing routine of noisy images as long as the noise is small. Sirisha et al (2014) have studied three different frameworks for detecting and retrieving near duplicate images and developed an approach to identify structure of dependency from the retrieved near duplicate images. The study revealed that the entire image-based framework does not retrieve images that diverse in intensity, contrast, rotation and cropping; the segmentbased framework does not retrieve images that vary in saturation, intensity, rotation and cropping; and the grid-based frame-work retrieves images with all variations.…”
Section: Introductionmentioning
confidence: 99%
“…The study justified that the use of blurring as a preprocessing routine of noisy images as long as the noise is small. Sirisha et al (2014) have studied three different frameworks for detecting and retrieving near duplicate images and developed an approach to identify structure of dependency from the retrieved near duplicate images. The study revealed that the entire image-based framework does not retrieve images that diverse in intensity, contrast, rotation and cropping; the segmentbased framework does not retrieve images that vary in saturation, intensity, rotation and cropping; and the grid-based frame-work retrieves images with all variations.…”
Section: Introductionmentioning
confidence: 99%